Trends of Taxation in Nepal: A Theoritical Review - Sharma, Yadab Raj (Academic Voices: A Multidisciplinary Journal, 2014)
This paper discusses the trends and strategies of taxation in Nepal. The trend towards the reform has been evident since the late 1970s, the process accelerated, however, since the mid 1980s. the urge and motivation for tax reform have come from a number of both internal and external factors. For this, changing perception of the role of government, desire to reduce macro economic imbalances, maintaining international competitiveness, increased Globalization of economic activity, demographic changes, foundation in theory and tax system in reality are the main impetus. But political instability has hampered creating an enabling environment for economic growth, investment and trade as well as revenue collection. Moreover, the adoption of the budget and the implementation of policies were delayed in the past due to unresolved disputes and demonstration. In recent years, reforms have been initiated by the Ministry of Finance to enhance the country's development but taxation is not free from challenges. So the paper ends by summarizing the challenges and strategies in the tax system of Nepal. Academic Voices, Vol. 3, No. 1, 2013, Pages 91-97 DOI: http://dx.doi.org/10.3126/av.v3i1.9987